SINTESIS SILIKA MESOPORI DENGAN CETAKAN GELATIN TULANG SAPI DAN KAPASITAS ADSORPSINYA TERHADAP METILEN BIRU - , ISABELA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis of mesoporous silica using gelatin template of bovine bones has been studied. Pretreatment with different combination of acid and/or base (HCl, HCl and NaOH, HCl-NaOH-acetic acid, HCl-NaOH-citric acid, HCl-KOH, HClKOH- acetic acid, and HCl-KOH-citric acid) were used before extract the gelatin to determine their effects on characteristic of bovine bone gelatin. The results of Fourier transform infrared spectroscopy (FTIR) characterization showed the functional region of gelatin molecule with the vibration peak at wave numbers of 3448-3325 cm -1 belong to the amide A, 2931-2368 cm -1 belong to the amide B, 1658-1635 cm -1 belong to the amide I, 1550-1327 cm -1 belong to the amide II, and 1242-509 cm -1 belong to the amide III. Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) analysis showed that all pretreatment process of bovine bones have alpha component of gelatin with molecular weight distribution at 120-160 kDa, except pretreatment with KOH and citric acid. The utilization of KOH and citric acid caused a significant amount of swelling of bovine bones pretreatment, related to further breakage of polypeptide chains to sub alpha chain with low molecular weight (<100 kDa). The gelatin of bovine bones with HCl pretreatment was used as a template to synthesize mesoporous silica with the gelatin/silica weight ratio 0.5 and 2.0 for sample 1 and 2. The mesoporous silica with surface area 362.878 m 2 /g and pore size about 7.048 nm were synthesized. The surface area increased with the increase of the gelatin/silica weight ratio. On the other hand, pore size and volume did not significantly influenced by the gelatin/silica weight ratio. The adsorption behavior of mesoporous silica towards methylene blue were consistent with the Langmuir and Freundlich models. The equilibrium of the adsorption process on sample 1 and 2 were achieved in 6 and 9 min, respectively. The adsorption capacities increases with increasing the homogenity of pore size distribution.